2006
DOI: 10.1159/000090936
|View full text |Cite
|
Sign up to set email alerts
|

Central Venous Line-Related Thrombosis in Children

Abstract: Central venous lines are used in critically ill children and in children with chronic conditions for the administration of intravenous therapy, such as fluids, medications, total parenteral nutrition and blood products. Although the use of central venous lines has greatly improved the quality of care in these children, these catheters may cause serious mechanical, infectious and thrombotic complications. The reported frequency of catheter thrombosis in children is low as 5% in studies including only symptomati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 104 publications
0
24
0
Order By: Relevance
“…This review will summarize the definition, risk factors and epidemiology of CRT in cancer patients, and review the evidence on prevention. It will focus largely on published data in adults, as CRT has a different natural history and a different prognosis in neonates and children [3]. Thrombotic complications of hemodialysis and apheresis catheters are not discussed.…”
Section: Introductionmentioning
confidence: 99%
“…This review will summarize the definition, risk factors and epidemiology of CRT in cancer patients, and review the evidence on prevention. It will focus largely on published data in adults, as CRT has a different natural history and a different prognosis in neonates and children [3]. Thrombotic complications of hemodialysis and apheresis catheters are not discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports are rare and almost exclusively in adults patients. However, venous obstruction is relatively common in pediatric patients with CVCs (unpublished data, [2]) and complications should be looked for.…”
Section: Discussionmentioning
confidence: 99%
“…The use of a central venous access device is the most significant cause of thromboembolic events in children, with incidence rates ranging from 8% to 25% [1,15,16]. The reported frequency of catheter thrombosis in children ranges from 5% in studies including only symptomatic cases up to 50% in studies in which patients are screened for catheter-related thrombosis [17]. A recent Cochrane Review found that the relative risk for central venous catheter thrombosis was lower using a subclavian compared with a femoral approach [18].…”
Section: Discussionmentioning
confidence: 99%